Potential of selected Senegalese Aedes spp. mosquitoes (Diptera: Culicidae) to transmit Zika virus - Diagne, Cheikh Tidiane (BMC Infect Dis, 2015)
BACKGROUND: Zika virus (ZIKV; genus Flavivirus, family Flaviviridae) is an emerging virus of medical importance maintained in a zoonotic cycle between arboreal Aedes spp. mosquitoes and nonhuman primates in African and Asian forests. Serological evidence and virus isolations have demonstrated widespread distribution of the virus in Senegal. Several mosquito species have been found naturally infected by ZIKV but little is known about their vector competence. METHODS: We assessed the vector competence of Ae. aegypti from Kedougou and Dakar, Ae. unilineatus, Ae. vittatus and Ae. luteocephalus from Kedougou in Senegal for 6 ZIKV strains using experimental oral infection. Fully engorged female mosquitoes were maintained in an environmental chamber set at 27 ± 1 °C and 80 ± 5 % Relative humidity. At day 5, 10 and 15 days post infection (dpi), individual mosquito saliva, legs/wings and bodies were tested for the presence of ZIKV genome using real time RT-PCR to estimate the infection, dissemination, and transmission rates. RESULTS: All the species tested were infected by all viral strains but only Ae. vittatus and Ae. luteocephalus were potentially capable of transmitting ZIKV after 15 dpi with 20 and 50 % of mosquitoes, respectively, delivering epidemic (HD 78788) and prototype (MR 766) ZIKV strains in saliva. CONCLUSION: All the species tested here were susceptible to oral infection of ZIKV but only a low proportion of Ae. vittatus and Ae. luteocephalus had the viral genome in their saliva and thus the potential to transmit the virus. Further investigations are needed on the vector competence of other species associated with ZIKV for better understanding of the ecology and epidemiology of this virus in Senegal. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12879-015-1231-2) contains supplementary material, which is available to authorized users.